IMPLEMENTASI KEBIJAKAN PERATURAN WALIKOTA BONTANG NOMOR 39 TAHUN 2011 TENTANG PEDOMAN PELAKSANAAN PROGRAM FASILITASI PARTISIPASI MASYARAKAT DALAM PERCEPATAN PEMBANGUNAN DI KECAMATAN BONTANG SELATAN - Heni Idris (Jurnal Paradigma (JP), 2017)
The purpose of this research is to describe the implementation of Mayor Bontang’s policy number 39/2011. The result show that the program of society participation which is held at South Bontang faced by the number of problems in implementation level, both administratively or technically. But it can contribute significantly to development acceleration.